Big Data Analysis for Predictive Healthcare Information System - Maurya, Neha; Tripathi, Anirudh; Singh, Pankaj Pratap; Kishor, Amit (International Journal of Computer Sciences and Engineering, 2019)
In the era of information, enormous different type of data has become available for decision making. Big data don’t refer to that data sets that is big, but also that is high in variety and velocity, which makes them hard to handle using by traditional tools and techniques. The quantity of data that we harvest and eat up is thriving aggressively in the digitized world. Increasing use of new innovations and social media generate vast amount of data that can earn splendid information if properly analysed. This large dataset generally known as big data, do not fit in traditional databases because of its’ rich size. Organizations need to manage and analyse big data for better decision making and outcomes. So, big data analytics is receiving a great deal of attention today. In healthcare, big data analytics has thepossibility of advanced patient care and clinical decision support. In this paper, we review the background and the various methods of big data analytics in healthcare. This paper also elaborates various platforms and algorithms for big data analytics and discussion on its advantages and challenges. This survey winds up with a discussion of challenges and future directions.